HER2-neu expression in Croatian breast cancer patients (results of one year multicentric prospective study) - Jakić Razumović, Jasminka; Šarčević, Božena; Šeparović, Viktor Kosanović , S; Boižkov, J Jonjić , Nives; Mustać, Elvira Tomić , Snježana; Bezić, Joško Krušlin, Božo, Vučić, Majda; Tomas, Davor Dmitrović , Branko; Blažičević, Valerija Jakovina, T; Švagelj, Dražen Borić, Igor; Njirić, Zdenko Štitić, V; Mlinac-Lucijanić, M Restek Samardžija, N; Predrijavec , H Gošev , M. (2005)
HER2-neu expression in Croatian breast cancer patients (results of one year multicentric prospective study).
ENG